Long-term treatment-free remission of chronic myeloid leukemia with falling levels of residual leukemic cells. Issue 12 (December 2018) - Ross, David; Pagani, Ilaria; Shanmuganathan, Naranie; Kok, Chung; Seymour, John; Mills, Anthony; Filshie, Robin; Arthur, Christopher; Dang, Phuong; Saunders, Verity; Braley, Jodi; Yong, Agnes; et al.
Abstract Following the achievement of deep molecular response on tyrosine kinase inhibitors (TKIs), approximately half of patients with chronic myeloid leukemia (CML) can discontinue TKI and remain in treatment-free remission (TFR). The ALLG CML8 study enrolled 40 imatinib-treated patients with undetectableBCR-ABL1 mRNA (approximately MR4.5 ). Molecular relapse was defined as detectableBCR-ABL1 on two consecutive tests or any single value >0.1%. With a median follow-up of 8.6 years (range 5.7–11.2 years), 18 patients remain in continuous TFR (45.0%; 95% confidence interval 31.9−63.4%). The latest relapse detected was 27 months after stopping imatinib. No patient progressed to advanced phase. Twenty-two patients met criteria for imatinib re-treatment and all regained undetectable molecular response. Nine patients in long-term TFR were monitored by highly sensitive individualizedBCR-ABL1 DNA PCR in a sufficient number of samples to enable more precise quantification of residual leukemia.BCR-ABL1 DNA decreased from a median of MR5.0 in the first year of TFR to MR6.1 in the sixth year of TFR. Our results support the long-term safety and remarkable stability of response after imatinib discontinuation in appropriately selected CML patients. Serial high sensitivity testing provides a new and unexpected finding of gradually reducing CML cells in patients in long-term TFR.